RELATIONSHIP BETWEEN ADMISSION POLICIES AND ACADEMIC PERFORMANCE OF UNDERGRADUATE STUDENTS IN FEDERAL UNIVERSITIES IN SOUTH-EAST GEOPOLITICAL ZONE OF NIGERIA (2010-2024) (Journal of the Management Sciences, 2026)
This study investigated admission Policies and academic performance of undergraduate students in federal universities in South East Geopolitical Zone of Nigeria (2010-2024). The Specific objectives of the study were to: examine the extent to which Merit-based admission policy relates to academic performance of undergraduate students; assess the extent of relationship between catchment area admission policy and academic performance of undergraduate students; and to ascertain the extent of relationship between educationally less developed states (ELDS) admission policy and academic performance of undergraduate students. The study was guided by three research questions and hypotheses. The population of the study comprised 21153 teaching and senior administrative staff of the five Federal Universities in the South-East Nigeria. Cross-sectional descriptive survey research design was adopted for the study. A sample size of 377 was determined using the Krejcie and Morgan (1970) statistical formula. The data required for the study were collected through a questionnaire instrument. Data analysis was done using descriptive and inferential statistics. Research questions were answered using mean, while hypotheses were tested using Pearson’s Product Moment Correlation at the 0.05 level of significance. Among the findings of the study were; Merit-based admission policy significantly and positively relates to academic Performance of undergraduate students; Catchment area admission policy significantly and positively relate to academic performance of undergraduate students; and ELDS admission policy significantly and positively relates to academic performance of undergraduate students in Federal Universities in South-East Geopolitical Zone of Nigeria. Based on the findings, the researcher therefore recommends among others; that Federal universities in the South-East geopolitical zone should prioritize merit-based admission policies; universities should maintain and strengthen these policies; ELDS (Educationally Less Developed States) admission policies, institutions should continue to support and enhance these initiatives
Keywords: Admission Policy; Students’ academic Performance; Federal Universities; Undergraduate Students